Misty - Clark, James B. 1908-2000; Sherdeman, Ted; Radnitz, Robert B.; Ladd, David, 1947-; O'Connell, Arthur, 1908-1981; Smith, Pam (Actress); Seymour, Anne, 1909-1988; Sawtell, Paul, 1906-1971; Shefter, Bert, 1902-1999; Tover, Leo, 1902-1964; Garmes, Lee, 1898-1978; Cramer, Duncan; et al. (Port Washington, NY Koch Vision, 2008)
Phantom, a rarely seen mare, eludes all efforts to capture her until a young brother and sister lay eyes on her. Although Phantom would forever be a creature of the wild, her gentle, loyal colt Misty is another story altogether.
Release date: Nov. 11, 2008.
Based on the novel Misty of Chincoteague by Marguerite Henry.
Originally released as a motion picture in 1961.
Includes trailer.
Music, Paul Sawtell and Bert Shefter ; directors of photography, Leo Tover, Lee Garmes ; art direction, Duncan Cramer, Maurice Ransford ; set decorations, Walter M. Scott, Stuart A. Reiss ; film editor, Fredrich Y. Smith.
David Ladd, Arthur O'Connell, Pam Smith, Anne Seymour, and the people of Chincoteague.
Keywords: Chincoteague pony -- Juvenile films; Ponies -- Juvenile films; Virginia -- Juvenile films; Feature films (M-Q); Feature films; Video recordings for the hearing impaired; Children's films; Fiction films; Film adaptations; Juvenile works